Combined TACE with Targeted and Immunotherapy versus TACE Alone Improves DFS in HCC with MVI: A Multicenter Propensity Score Matching Study - Chen X; Wu X; Peng W; Liu L; Liu X; Wan X; Xu H; Zheng Y; Zhao H; Mao Y; Lu X; Sang X; et al. (Journal of Hepatocellular Carcinoma)
Xiaokun Chen,1,2,* Xiangan Wu,1,2,* Wei Peng,3– 5 Liguo Liu,6 Xiao Liu,1 Xueshuai Wan,1 Haifeng Xu,1 Yongchang Zheng,1 Haitao Zhao,1 Yilei Mao,1 Xin Lu,1 Xinting Sang,1 Xiaoyan Chang,7 Kang Zhou,8 Jie Pan,8 Mei Guan,9 Dandan Hu,3– 5 Haidong Tan,6 Yaojun Zhang,3– 5 Shunda Du1 1Department of Liver Surgery, Peking Union Medical College Hospital, Peking Union Medical College and Chinese Academy of Medical Sciences, Beijing, 100005, People’s Republic of China; 2Graduate School, Peking Union Medical College and Chinese Academy of Medical Sciences, Beijing, 100006, People’s Republic of China; 3Department of Liver Surgery, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, 510060, People’s Republic of China; 4Collaborative Innovation Center for Cancer Medicine, State Key Laboratory of Oncology in South China, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, 510060, People’s Republic of China; 5State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for Cancer, Collaborative Innovation Center for Cancer Medicine, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, 510060, People’s Republic of China; 6Second Division of Hepatopancreatobiliary Surgery, China–Japan Friendship Hospital, Beijing, 100029, People’s Republic of China; 7Department of Pathology, Peking Union Medical College Hospital, Peking Union Medical College and Chinese Academy of Medical Sciences, Beijing, 100005, People’s Republic of China; 8Department of Radiology, Peking Union Medical College Hospital, Peking Union Medical College and Chinese Academy of Medical Sciences, Beijing, 100005, People’s Republic of China; 9Department of Medical Oncology, Peking Union Medical College Hospital, Peking Union Medical College and Chinese Academy of Medical Sciences, Beijing, 100005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shunda Du, Email dushd@pumch.cn Yaojun Zhang, Email zhangyuj@sysucc.org.cnBackground: Hepatocellular carcinoma (HCC) with microvascular invasion (MVI) is associated with high recurrence and poor survival outcomes. Although adjuvant therapies such as transcatheter arterial chemoembolization (TACE), targeted therapy, and immunotherapy show potential in improving outcomes, the optimal postoperative treatment strategy remains undetermined. This study evaluates the efficacy of different adjuvant treatments on disease-free survival (DFS) and overall survival (OS) in HCC patients with MVI following curative resection.Methods: A retrospective cohort of 409 HCC patients with MVI who underwent curative resection from three clinical centers between 2017 and 2024 was analyzed. Patients were stratified into three groups: TACE alone (n=132), TACE + targeted therapy (n=58), and TACE + targeted immunotherapy (n=68). Propensity score matching (PSM) was employed to balance confounding factors. Kaplan-Meier survival curves and Cox regression models were used to assess DFS and OS. A nomogram was constructed for individualized DFS prediction.Results: After PSM, both the TACE + targeted therapy and TACE + targeted immunotherapy groups exhibited significantly prolonged DFS compared to TACE alone (median DFS: 16 vs 22 and 21 months, respectively; p=0.027). No significant differences were observed in OS across the groups. The nomogram for DFS demonstrated robust predictive performance, with a C-index of 0.709 and 0.645 in the training and validation cohorts, respectively, supporting its utility in clinical decision-making.Conclusion: In HCC patients with MVI, adjuvant TACE combined with targeted therapy or targeted immunotherapy significantly enhances DFS, though no OS benefit was observed. The developed nomogram provides a reliable tool for risk stratification and personalized postoperative management in this high-risk patient population.Keywords: hepatocellular carcinoma, microvascular invasion, postoperative adjuvant therapy, targeted therapy, immunotherapy, transcatheter arterial chemoembolization